Costs of cloud IAAS in businesses - Kučera, Adam (2016)
Cloud computing brings many possibilities for businesses, large or small, which they can leverage for reduction of their IT infrastructure costs. This thesis presents the key concepts of cloud computing and its main advantages and disadvantages for enterprises. It compares different cloud IAAS providers and presents a framework for comparison of classic on-premises infrastructure costs and Infrastructure as a Service costs.